Teachers’ Perspective on the Implementation of Merdeka and K-12 English Curricula - Valmeo, Christinelle; Suwartono, Tono; Suhail, Ayesha (Universitas Jambi, Magister Program of English Education Department, 2026)
English language curriculum reform has become increasingly important in Southeast Asia as countries seek to enhance learners’ communicative competence and global competitiveness. Although studies have been done on Indonesia’s Merdeka Curriculum and the K to 12 Curriculum of the Philippines, most studies have examined these curricula separately, and the focus has mostly been on policy formulation rather than curriculum implementation. This article attempts to fill this gap by exploring the implementation of these two curricula particularly in terms of learning objectives, content, pedagogy, and assessment from the teachers’ perspectives. Using a qualitative comparative case study design, data were collected through semi-structured interviews with 10 secondary English teachers from the Philippines and Indonesia (five teachers from each country), questionnaires, and document analysis. Thematic analysis indicated that both curricula promote communicative competence and develop learners’ macro language skills. Indonesian participants perceived the Merdeka Curriculum as emphasizing flexibility, learner autonomy, and real-world communication. On the other hand, the K to 12 Curriculum highlights academic literacy, competencies, and preparation for higher education. In addition, both contexts had similar issues in implementing curricula, including challenges with mixed-ability classrooms, lack of time, and assessment. The study also contributes to curriculum implementation literature by proposing a comparative Curriculum Implementation Framework that explains how curriculum policy orientation shapes teacher agency and curriculum enactment across different educational contexts. In conclusion, the findings suggest that a balance between curriculum flexibility and clear standards may support effective English language teaching in these contexts.